HE LATE PHILOSOPHY OF GEORG LUKÁCS: HISTORY, FETISHISM AND ALIENATION - NICHITEAN, Cristian (Studia Universitatis Babeș-Bolyai Philosophia, 2016)
The Late Philosophy of Georg Lukács: History, Fetishism and Alienation. Lukács’s late ontological turn is an attempt to go beyond the limitations of his early thesis of the identical subject-object and to better understand those forms of objectivity that appear as a consequence of social existence. In this category of social forms of objectivity he includes the phenomena of fetishism and reification, determined by the dual character, simultaneously material and social, of the objects produced under the rule of commodity form and of exchange value. Closeley related is the phenomenon of alienation, caused by the difference between the developement of society and that of human personality, crushed under the weight of fetishism.